Association of uromodulin with acute kidney injury in patients undergoing cardiac surgery - Chojęta, Dariusz; Kozioł, Małgorzata; Targońska, Sylwia; Smarz-Widelska, Iwona (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2020)
Uromodulin (Umod) is a protein produced exclusively in the kidneys, and it is the most abundant protein in human urine. Scientific studies show that it can be a valuable diagnostic tool in monitoring kidney function. Clinical applications of Umod are probably wider. One of them is the role of a biomarker in cardiac surgery-associated acute kidney injury (CSA-AKI). Data from scientific studies indicate that a lower level of Umod in urine prior to surgery is associated with a higher risk of developing CSA-AKI after the procedure. A higher serum Umod level is suspected to be a good prognostic factor in the context of renal healing. It seems that the current state of knowledge supports the protective role of Umod in the course of AKI. Large, multi-center clinical trials would allow for the consolidation of preliminary scientific data and a more accurate understanding of the role of Umod as a CSA-AKI biomarker.